Job satisfaction and its associated factors among health care workers in Saint Paul’s Hospital Millennium Medical College, Ethiopia - Melese Bahiru Tesema; Berhanu Teshome Woldeamanuel; Amideyesus Adinaw Lopiso; Muluye Abebe Beyene (PLoS ONE, 2025)
Background Job satisfaction, a positive emotional state from evaluating work experiences, has a global prevalence of 46.68% among healthcare workers, often lower than other public servants due to challenging conditions. Improving job satisfaction is vital for better healthcare services. However, information on the level of job satisfaction among health professionals in Ethiopia remains scarce. This study sought to assess job satisfaction and its associated factors among health professionals at Saint Paul’s Hospital Millennium Medical College in Addis Ababa, Ethiopia. Methods An institution-based cross-sectional study was conducted from April 03/2023 to May 10/2023, involving 439 randomly selected healthcare workers. Data collection utilized the interviewer-administered Minnesota Satisfaction Questionnaire. Ordinal logistic regression was applied to identify factors associated with job satisfaction. Statistical significance was determined by a p-value of less than 0.05 or a 95% confidence interval for the adjusted odds ratio excluding one. Results All 439 healthcare workers participated, achieving a 100% response rate. Job satisfaction levels were categorized as very dissatisfied (27.1%), dissatisfied (26.2%), satisfied (24.8%), and very satisfied (21.9%). Factors associated with decreased job satisfaction included a monthly salary below 8,000 ETB (AOR = 0.377, CI: 0.174–0.814), salary of 8,000–10,000 ETB (AOR = 0.249, CI: 0.117–0.571), history of headaches (AOR = 0.607, CI: 0.406–0.908), working in emergency (AOR = 0.205, CI: 0.084–0.502), inpatient (AOR = 0.391, CI: 0.167–0.916), or radiology environments (AOR = 0.081, CI: 0.013–0.489). Increased job satisfaction was linked to nursing (AOR = 1.679, CI: 1.011–2.787) and radiology professions (AOR = 35.21, CI: 4.14–299.39). Conclusion Factors such as low salary and high-stress work environments reduce job satisfaction, necessitating strategies to improve workplace conditions and revise salary structures to foster greater satisfaction among healthcare workers. The hospital should address high-stress environments like emergency and inpatient settings and offer support to healthcare workers with headaches. Moreover, the Ministry of Health should revise salary structures and assess work environments to enhance healthcare workers’ job satisfaction.